Interaction of antibacterial compounds with RND efflux pumps in Pseudomonas aeruginosa - Dreier, Juerg; Ruggerone, Paolo (Frontiers in Microbiology, 2015)
Pseudomonas aeruginosa infections are becoming increasingly difficult to treat due to intrinsic antibiotic resistance and the propensity of this pathogen to accumulate diverse resistance mechanisms. Hyperexpression of efflux pumps of the Resistance-Nodulation-Division-type multidrug efflux pumps (e.g. MexAB-OprM), chromosomally encoded by mexAB-oprM, mexCD-oprJ, mexEF-oprN, and mexXY (-oprA) is often detected in clinical isolates and contributes to worrying multi-drug resistance phenotypes. Not all antibiotics are affected to the same extent by the aforementioned RND efflux pumps. The impact of efflux on antibiotic activity varies not only between different classes of antibiotics but also between members of the same family of antibiotics. Subtle differences in physicochemical features of compound-pump and compound-solvent interactions largely determine how compounds are affected by efflux activity. The combination of different high-resolution techniques helps to gain insight into the functioning of these molecular machineries. This review discusses substrate recognition patterns based on experimental evidence and computer simulations with a focus on MexB, the pump subunit of the main RND transporter in P. aeruginosa.